The Emerging Role of STING in Insect Innate Immune Responses and Pathogen Evasion Strategies - Liu, Qiuning; Kausar, Saima; Tang, Yingyu; Huang, Wuren; Tang, Boping; Abbas, Muhammad Nadeem; Dai, Lishang (Frontiers in Immunology, 2022)
Emerging evidence reveals that the stimulator of the interferon genes (STING) signaling pathway in insects and other animal cells helps them to sense and effectively respond to infection caused by numerous types of microbial pathogens. Recent studies have shown that genomic material from microbial pathogens induces the STING signaling pathway for the production of immune factors to attenuate infection. In contrast, microbial pathogens are equipped with various factors that assist them in evading the STING signaling cascade. Here we discuss the STING signaling pathway different animal groups compared to human and then focus on its crucial biological roles and application in the microbial infection of insects. In addition, we examine the negative and positive modulators of the STING signaling cascade. Finally, we describe the microbial pathogen strategies to evade this signaling cascade for successful invasion.